Possible Involvement of Hsp90 in the Regulation of Telomere Length and Telomerase Activity During the Leishmania amazonensis Developmental Cycle and Population Proliferation - de Oliveira, Beatriz C. D.; Shiburah, Mark E.; Paiva, Stephany C.; Vieira, Marina R.; Morea, Edna Gicela O.; da Silva, Marcelo Santos; Alves, Cristiane de Santis; Segatto, Marcela; Gutierrez-Rodrigues, Fernanda; Borges, Júlio C.; Calado, Rodrigo T.; Cano, Maria Isabel N. (Frontiers in Cell and Developmental Biology, 2021)
The Leishmania developmental cycle comprises three main life forms in two hosts, indicating that the parasite is continually challenged due to drastic environmental changes. The disruption of this cycle is critical for discovering new therapies to eradicate leishmaniasis, a neglected disease that affects millions worldwide. Telomeres, the physical ends of chromosomes, maintain genome stability and cell proliferation and are potential antiparasitic drug targets. Therefore, understanding how telomere length is regulated during parasite development is vital. Here, we show that telomeres form clusters spread in the nucleoplasm of the three parasite life forms. We also observed that amastigotes telomeres are shorter than metacyclic and procyclic promastigotes and that in parasites with continuous in vitro passages, telomere length increases over time. These observed differences in telomere length among parasite’s life stages were not due to lack/inhibition of telomerase since enzyme activity was detected in all parasite life stages, although the catalysis was temperature-dependent. These data led us to test if, similar to other eukaryotes, parasite telomere length maintenance could be regulated by Hsp83, the ortholog of Hsp90 in trypanosomatids, and Leishmania (LHsp90). Parasites were then treated with the Hsp90 inhibitor 17AAG. The results showed that 17AAG disturbed parasite growth, induced accumulation into G2/M phases, and telomere shortening in a time-dependent manner. It has also inhibited procyclic promastigote’s telomerase activity. Besides, LHsp90 interacts with the telomerase TERT component as shown by immunoprecipitation, strongly suggesting a new role for LHsp90 as a parasite telomerase component involved in controlling telomere length maintenance and parasite life span.